Contemporary research in e-branding - Bandyopadhyay, Subir, 1958- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
This book presents research on the global issue of the Internet as a central organizing platform for integrating marketing communications and on using e-Branding to increase the visibility and success of companies in all business realms.